Effects of Seasonal Variations in Physical Parameters on Quality of Gravity Flow Water in Kyanamira Sub-County, Kabale District, Uganda - Ngabirano, Hannington; Byamugisha, Denis; Ntambi, Emmanuel (Journal of Water Resource and Protection, 2016)
The effect of seasonal variations in physical parameters on quality of gravity flow water was investigated in Kyanamira Sub-County, Kabale District, Uganda. The seasonal variations in the physical parameters (pH, temperature, electrical conductivity (EC), turbidity, colour, total dissolved solids (TDS), and total suspended solids (TSS)) were determined during wet and dry seasons. Composite samples from gravity flow water sources were collected monthly from March to August, 2014 and then analyzed. Temperature was measured using thermometer; pH, EC and TDS were determined using a multimeter, turbidity, colour and total suspended solids were determined by spectrophotometric method. TDS, pH and temperature were the most contributing parameters to water quality variations in both seasons. The mean pH values varied between 3.78 - 4.84 from March to August, 2014 at all study sites. These pH values were consistently below the WHO permissible range of 6.5 - 8.5. Similarly, total suspended solids varied between 0.66 - 2.17 mg∙L−1 and were well above the recommended WHO limit of zero mg∙L−1 at all study sites. Turbidity mean values varied between 0.83 - 3.7 NTU and were outside the recommended limits of 3 NTU at Kigata (3.7 NTU) only. Temperatures (20.3˚C - 21.15˚C) for all the study sites were within the parameters for the wet season were: temperature (21.12˚C), colour (12.5 PtCoU), turbidity (3.4 NTU), TDS (76.76 mg∙L−1), TSS (2.13 mg∙L−1), pH (4.19) and EC (152.7 μS∙cm−1) were different from those of the dry season (temperature (20.99˚C), colour (0.93 PtCoU), turbidity (0.53 NTU), TDS (77.33 mg∙L−1), TSS (0.67 mg∙L−1), pH (4.86) and EC (158.65 μS∙cm−1). Basing on these findings above, it was evident to justify discouraging the use of gravity flow water at these study sites for domestic purposes without proper treatment.
Keywords: Kyanamira Sub-County; Seasonal Variations; Gravity Flow Water; Gravity Flow Water